KARAKTERISTIK BUAH DAN BIJI KAKAO (Theobroma cacao L.) PADA BERBAGAI ALTITUDE DI DATARAN TINGGI HUMBAHAS - Sitohang, Nurdin (LPPM Universitas Katolik Santo Thomas Medan, 2023)
The cocoa beans of small holder were usually still low quality, one of it caused by planting location of various altitude. The focus of this research were characteristic of cocoa pod and beans on several altitudes in Humbahas highland. The research method were survey as purposive sampling on four altitudes as 865, 960, 1030, and 1118 m from sea levels. The observed parameters were pod size, pod diametre, pod volume, dry weight of pods, dry weight of kolven, dry weight of beans, bean count per pod, and dry weight per bean at 4 different altitudes in Humbahas highland (>800 m asl) with 10 pods (replications) at each altitudes. The results of research showed that: pod size increased, pod diametre increased, pod dry weight increased, dry weight of beans increased, bean count per pod increased, and dry weight each bean increased with the increasing of altitude. The best pods and beans were at altitude of 960 m asl, namely fruit length 18.10 cm, fruit dry weight 85,92 g, beans dry weight 39,02 g, number of beans per fruit 38,7 and average weight per bean 1,02 g. The physical characteristics of cocoa pods and beans are still in the normal category.